Viability of Microencapsulated Probiotics in Cross-Linked Alginate Matrices and Chia Seed or Flaxseed Mucilage During Spray-Drying and Storage - Mariela Bustamante; B. Dave Oomah; César Burgos-Díaz; Daniela Vergara; Liset Flores; Carolina Shene (Microorganisms)
Interest in probiotics has not diminished, and techniques to protect them from the environment in which they are found are constantly being innovated. Spray-drying is the most studied and industrially used technique to encapsulate probiotics. Recently, a new process has been developed in which particle formation, alginate cross-linking, and drying are carried out in a single step. In this study, Bifidobacterium infantis, Bifidobacterium longum, Lactobacillus plantarum, and Lactobacillus rhamnosus were microencapsulated by spray-drying using a cross-linked alginate matrix supplemented with chia seed mucilage (CM) or flaxseed mucilage (FM) as the coating material. All formulations evaluated, supplemented with 0.4% (w/v) of CM or FM, including the control formulation showed high survival rates, varying between 87% and 97%. The viability of microencapsulated probiotics was affected by storage temperature. At 4 °C, viability decreased slightly, and after 90 days, the viable probiotic count ranged from 7 to 11 Log CFU/g of dry powder. Meanwhile, viability did not exceed 4 Log CFU/g of dry powder at 37 °C. Probiotic microencapsulation in cross-linked alginate matrices and chia or flaxseed mucilage by spray-drying is presented as a promising alternative for their protection, potentially improving the long-term stability and efficacy of the probiotic product.